Cultivation With Powdered Meteorite (NWA 1172) as the Substrate Enhances Low-Temperature Preservation of the Extreme Thermoacidophile Metallosphaera sedula - Milojevic, Tetyana; Zebec, Ziga; Schimak, Mario P. (Frontiers in Astronomy and Space Sciences, 2020)
Recent studies have uncovered a vast number of thermophilic species in icy environments, permanently cold ocean sediments, cold sea waters, and cool soils. The survival of thermophiles in psychrobiotic habitats requires thorough investigation of the physiological and molecular mechanisms behind their natural cryopreservation. Such investigations are mainly impeded due to a restricted cultivation of thermophiles at low temperatures under the laboratory conditions. Artificial culture media used under the laboratory conditions usually fail to support cultivation of thermophiles at low-temperature range. In this study we cultivated the extreme thermoacidophilic archaeon Metallosphaera sedula with the preliminary powdered and sterilized multimetallic extraterrestrial mineral material (the meteorite NWA 1172) under a low temperature regime in laboratory conditions. Our data indicate that M. sedula withstands cold stress and can be maintained at low temperatures, when supplemented with the meteorite NWA 1172 as the sole energy source. Cultivation with the meteorite NWA 1172 opens up new, previously unknown psychrotolerant characteristics of M. sedula, emphasizing that culture conditions (i.e., the "nutritional environment") may affect the microbial survival potential in stress related situations. These observations facilitate further investigation of strategies and underlying molecular mechanisms of the survival of thermophilic species in permanently cold habitats.